Influence of different air supply parameters on indoor thermal comfort of upper air supply room. Issue 1 (June 2021) - Xiang, Pei; Dong, Min; Huo, Nengmeng; Xu, Chuanliang; Yang, Fengluan
Abstract: The temperature field, velocity field and PMV evaluation indexes under different air supply parameters are calculated by using Airpack software to divide grids and carry out numerical simulation. The cloud maps of evaluation indexes for different air supply parameters are compared and analyzed. The result determines the optimal air supply parameters.